Fusarium Rot Biological Control of Citrus caused by Fusarium oxysporum - Dewi, Ovilya Kusuma Minarma; Abadi, Abdul Latief; Widyaningsih, Sri (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
Fusarium oxysporum is a pathogen that causes Fusarium rot disease on citrus plants. The F. oxysporum is a soil-borne pathogen whose fungicide is not effective against it and difficult to cure. Thus, the use of Trichoderma spp. as one of the most effective and well-known biocontrol agents against many plant diseases in agriculture is needed. To test Trichoderma capabilities on the specific pathogen, method of this study consisted of isolation and rejuvenation of F. oxysporum and Trichoderma, morphological identification of the fungus, in vitro test of Trichoderma antagonistic ability against F. oxysporum on PDA medium, and in vivo test conducted in a green house on Rough Lemon (RL) and Japansche Citroen (JC) rootstock seeds to calculate the total disease incidence using a formula. The result of in vitro test of this study shows that 3 Trichoderma isolates (TJ, TKH, and TST) were able to inhibit the growth of F. oxysporum on PDA medium by 65.56%, 62.99%, and 61.19%, respectively. While in vivo test shows that the treatment of TJ isolates on RL seeds and TKH on JC seeds shows lowest disease incidence percentage of 3.33%. Therefore, this study proves that Trichoderma can be used as a biocontrol agent in controlling Fusarium rot disease in citrus plants. However, further research is needed to detect which Trichoderma species TJ and TKH isolates contain.